A Rare Cause of Cavitary Lesion in the Lung: Richter’s Transformation - Fatma Yıldırım; İskender Kara; Sedat Yıldız; Nalan Akyürek; Kadir Acar; Melda Türkoglu; Gülbin Aygencel (Case Reports in Pulmonology)
Richter’s transformation (RT) refers to the development of aggressive lymphoma during the course of CLL. Clinically, patients with RT present with an aggressive disease course with rapidly enlarging lymph nodes, hepatosplenomegaly, and elevated serum lactate dehydrogenase levels. But rarely it presents with extra nodal organ involvement at the beginning. Common sites of extra nodal involvement are the gastrointestinal tract, eye, central nervous system, lung, and kidney. We are reporting this case that was presented with RT in the lung involvement diagnosed while researching cavitary lesion etiology.